Ectopic cutaneous schistosomiasis - Case report - Kathia Monielly Tenorio Nunes; Alberto Eduardo Cox Cardoso; Fabio de Souza Guedes Pereira; Luiz Henrique Carvalho Batista; Ricardo Luiz Simoes Houly (Sociedade Brasileira de Dermatologia, 2013)
Schistosomiasis mansoni is a systemic disease caused by a helminth of the schistosoma genus. The disease is generally asymptomatic or gastrointestinal symptoms may predominate. Skin lesions related to the disease are rarely diagnosed, even in endemic areas. The authors report the case of a young girl diagnosed with cutaneous schistosomiasis with involvement of the abdomen, back and scapular region. Schistosoma eggs were found in the lesions by histopathologic exam. There was no evidence of systemic involvement. Schistosomiasis must be included in the list of differential diagnosis of skin damage, especially in endemic areas, due to the potential consequences, in case of late diagnosis and treatment.